Diagnostic disclosure in Alzheimer's disease: A review - Irina Raicher; Paulo Caramelli (Dementia & Neuropsychologia)
Abstract Although growing, the literature on research into attitudes of general and specialized physicians towards disclosing the diagnosis of dementia and Alzheimer's disease (AD), or the current practice on AD disclosure, remains limited. Moreover, information is also scarce on what caregivers, or indeed patients themselves, wish to know with regard to their diagnosis. The goal of the present article was to present a review of the current available literature on the topic of truth telling in dementia, especially in AD. The studies discussed in this review were mainly conducted in Europe, particularly in the United Kingdom, as well as the United States. Disclosure of AD diagnosis is not a common practice among physicians. In the clinical context, the discussion on diagnosis disclosure can be valuable for improving the care of AD patients and their families.